Islamic Social Responsibility, Islamic Corporate Governance, Manajemen Laba, dan Kinerja Keuangan Pada Perusahaan Syariah - Putri Salbiah Sukma Br. Nst; Sri Rahayu; Jalilah Ilmiha (Journal of Trends Economics and Accounting Research, 2026)
This study aims to examine the effect of Islamic Corporate Social Responsibility (ICSR) and Islamic Corporate Governance (ICG) on financial performance with earnings management as a moderating variable in sharia public companies within the financial and banking sector listed in the Sharia Securities List during the 2020–2024 period. This study employed a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sampling technique used purposive sampling, resulting in 30 observations. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS version 25. The results indicate that ICSR has a positive and significant effect on financial performance, with a regression coefficient of 18.558 and a significance value of 0.029 (< 0.05). In contrast, ICG does not have a significant effect on financial performance, as indicated by a significance value of 0.200 (> 0.05). Earnings management also does not significantly affect financial performance, with a significance value of 0.678 (> 0.05). Furthermore, earnings management is unable to moderate the relationship between ICSR and ICG on financial performance because the significance values of the interaction variables are 0.435 and 0.449 (> 0.05), respectively. The coefficient of determination test shows an Adjusted R Square value of 0.028 or 2.8%, indicating that the research variables explain only 2.8% of the variation in financial performance, while the remaining 97.2% is influenced by other factors outside the research model. These findings demonstrate that sharia-based social responsibility disclosure plays a more dominant role than sharia governance mechanisms in improving the financial performance of sharia companies.